Little girls can be mean : four steps to bully-proof girls in the early grades - Anthony, Michelle (St. Martin's Griffin, 2010)
"In today's world, girls are facing myriad friendship issues, including bulling and cliques. As a parent, you are likely wondering how to guide your daughter through these situations effectively. 'Little Girls Can Be Mean' is the first book to tackle the unique social struggles of elementary-aged girls, giving you the tools to help your child become stronger, happier, and better able to enjoy friendships and handle social cruelty"--Back cover.